Peningkatan Daya Saing Produk Melalui Pelatihan Pengemasan Sabun Cuci Piring Pada Kelompok PKK RT 06 Kelurahan Jaya Mukti Kota Dumai - Fitra Fitra; Trisna Mesra; Nuryasin Abdillah; Melliana Melliana; Azmi Azmi; Hanifatul Rahmi (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2026)
This community service activity aimed to improve the knowledge and skills of members of PKK RT 06, Jaya Mukti Village, Dumai City, in product packaging and labeling as an effort to enhance the competitiveness of dishwashing liquid products. The activity involved 40 participants and was conducted using a participatory approach through counseling, demonstrations, hands-on practice, and mentoring. Training materials covered the functions and benefits of packaging, packaging design, product labeling, branding, and packaging techniques suitable for dishwashing liquid products. The results showed that participants experienced an increase in understanding regarding the role of packaging as a marketing tool and a value-added component of products. Participants were able to select appropriate packaging, design simple product labels, and apply packaging techniques to improve product appearance and identity. The packaging and labeling practices produced dishwashing liquid products with a more attractive, informative, and marketable appearance compared to their previous condition. The activity also increased participants’ awareness of the importance of branding and product differentiation in supporting household-based business development. Overall, the training successfully enhanced participants’ capacity in packaging and labeling, contributing to improved product competitiveness and supporting community economic empowerment.